Malic enzyme 1 is important for uterine decidualization in response to progesterone/cAMP/PKA/HB‐EGF pathway. Issue 3 (15th January 2020) - Yu, Hai‐Fan; Duan, Cui‐Cui; Yang, Zhan‐Qing; Wang, Yu‐Si; Yue, Zhan‐Peng; Guo, Bin
Abstract: Malic enzyme 1 (Me1), a member of the malic enzymes involving in glycolytic pathway and citric acid cycle, is essential for the energy metabolism and maintenance of intracellular redox balance state, but its physiological role and regulatory mechanism in the uterine decidualization are still unknown. Current study showed that Me1 was strongly expressed in decidual cells, and could promote the proliferation and differentiation of stromal cells followed by an accelerated cell cycle transition, indicating an importance of Me1 in the uterine decidualization. Silencing of Me1 attenuated NADPH generation and reduced GR activity, while addition of NADPH improved the defect of GR activity elicited by Me1 depletion. Further analysis found that Me1 modulated intracellular GSH content via GR. Meanwhile, Me1 played a role in maintaining mitochondrial function as indicated by these observations that blockadge of Me1 led to the accumulation of mitochondrial O 2 - level and decreased ATP production and mtDNA copy numbers accompanied with defective mitochondrial membrane potential. In uterine stromal cells, progesterone induced Me1 expression through PR‐cAMP‐PKA pathway. Knockdown of HB‐EGF might impede the regulation of progesterone and cAMP on Me1. Collectively, Me1 is essential for uterine decidualization in response to progesterone/cAMP/PKA/HB‐EGF pathway and plays an important role in preventing mitochondrial dysfunction.